Deformation of nickel-titanium closed coil springs: An in vitro study - Vieira, Camilla Ivini Viana [UNESP]; Reis, José Maurício Dos Santos Nunes [UNESP]; Vaz, Luiz Geraldo [UNESP]; Martins, Lídia Parsekian [UNESP]; Martins, Renato Parsekian [UNESP] (FapUNIFESP (SciELO), 2017)
Objective: The aim of this paper was to determine the amount of deformation in four commercial brands of nickel-titanium closed springs. Methods: A total of 130 springs were divided into 13 subgroups, according to their features and manufacturers (Morelli, Orthometric, Ormco and GAC) and activated from 100% to 1000% of the effective length of the nickel-titanium portion present at the spring, at 37 °C. Deactivation data were plotted and deformation was found graphically. The values were compared by analysis of variance and Tukey’s post-hoc test. Results: Springs manufactured by Morelli had the same amount of deformation when they were activated up to 700% of Y activation; springs by Orthometric had the same amount of deformation up to 600-700% of Y; springs by Ormco had the same amount of deformation up to 700-800% of Y; and finally, the majority of springs by GAC had similar deformation up to 800%-1000% of activation. All springs tested could be activated up to 700% without rupture. Conclusions: Most subgroups were similarly deformed up to 700% of activation, without rupture of springs. Subgroups 4B, 4C, 4D and 4E showed the same amount of deformation up to 1000% of activation without any rupture at all.
Keywords: Biomechanics; Deformation; NiTi